Combined Aerobic and Physicochemical Treatment of Pharmaceutical Industry Sludge - Asia, I. O.; Ademoroti, c. M. A. (Biological Sciences - PJSIR, 2005)
Composite samples of sludge obtained from a pharmaceutical factory were analysed for their pollution cha- racteristics. The samples were then treated by integrated aerobic biological and physicochemical methods. The analysis revealed that the BOD and COD of the sludge liquor were high, as well as were the levels of solids concentration, nit- rogen, phosphorus and bacterial count. These showed that sludge from this industry had a high pollution potential, and therefore needed treatment before disposal or reuse in other applications. Percentage solids reduction achieved were in the range of 26.1 to 29% of total soluble solids, 26.1 to 33% of suspended solids, and 43 to 52% of volatile solids. BOD and COD reductions were in the range of 96.1 to 98.2%, and 96.8 to 98.4%, respectively. Ammonia nitrogen reductions in this sludge were about 85.2 to 93.3%. Total nitrogen and phosphorus were also found to be appreciably reduced by the combined aerobic and physicochemical treatment methods